2005
DOI: 10.1017/s0021900200000851
|View full text |Cite
|
Sign up to set email alerts
|

A sufficient condition for the existence of an invariant probability measure for Markov processes

Abstract: In this paper, it is shown that the Foster-Lyapunov criterion is sufficient to ensure the existence of an invariant probability measure for both discrete-and continuous-time Markov processes without any additional hypotheses (such as irreducibility).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…where C is a petite set for {X t } t∈R + (since it is petite for R), from which the 'if' part of the result follows. The converse result is Theorem 4.1 of Costa and Dufour (2005a).…”
Section: Doeblin Decomposition and Lyapunov Criterionmentioning
confidence: 90%
“…where C is a petite set for {X t } t∈R + (since it is petite for R), from which the 'if' part of the result follows. The converse result is Theorem 4.1 of Costa and Dufour (2005a).…”
Section: Doeblin Decomposition and Lyapunov Criterionmentioning
confidence: 90%
“…Moreover, if ∞ 0 ds B(s) = ∞ and A < 0, then W is a compact function and by the Itô formula the solution is non-explosive with EW (X t ) < ∞, t ≥ 0. Thus, according to [4,Theorem 4.1], A < 0 also implies that the associated Markov semigroup has an invariant probability measure. Below we prove that L W is locally bounded such that (3.2) holds.…”
Section: The Semigroup φ-Entropy Inequalitymentioning
confidence: 99%
“…Theorems 2.1(i) and 2.2(i) in [6] An important feature of our Theorems 4, 5, and 6 for establishing positive Harris recurrence and geometric ergodicity is that they do not require the Markov chain to be ψ-irreducible. Costa and Dufour [1] also showed that the ψ-irreducibility assumption is not needed for the one-step drift condition for positive Harris recurrence. Another subtlety in their drift condition is that it uses extended real-valued test functions -our conditions, and those in [6], simply use real-valued test functions.…”
Section: Introductionmentioning
confidence: 99%